Effectiveness of Massive Open Online Course on Risk Communication Knowledge in Global Health Emergencies Among Nurses - Khin Thandar Aung; Rafiza Abdul Razak; Muhammad Fadli Zulkafley (Jurnal Keperawatan Indonesia)
Massive Open Online Courses (MOOCs) have transformed education. The minimal usage of MOOCs in nursing education reveals a lack of continuous healthcare professional development. Although MOOCs are recognized as a viable means of continuing education for healthcare professionals, their application and content specifically tailored to healthcare have remained unexplored. This study aimed to determine the effectiveness of a dedicated Massive Open Online Course (MOOC) designed to enhance nurses' risk communication knowledge in global health emergencies through testing with a small nurse sample in a pilot trial. This preliminary examination seeks participant feedback and insights. A quasi-experimental research design was conducted, employing a one-group pre-test and post-test design using the convenience sampling method with 40 registered nurses from the medical center of International Islamic University Malaysia. These nurses engaged in a four-week MOOC hosted on i-Taleem (the university's eLearning platform), focusing on knowledge about risk communication. Pre- and post-course questionnaires were administered, and the data was analyzed using SPSS version 20.0's paired t-test. The study showed a significant improvement in test scores with a p-value of 0.022, which is less than the predetermined significance level of 0.05. Consequently, the alternate hypothesis (HA) is accepted, signifying a substantial improvement in nurses' knowledge of risk communication in global health emergencies. Additionally, this study provides the framework for the widespread implementation of such instructional interventions in nursing education and professional development.